"There are No Votes in Africa"?: Australia, Africa and the UN Security Council. (21st April 2020) - Mickler, David; PijoviĆ, Nikola
Abstract : This article examines how Australia's successful campaign for a non‐permanent seat on the United Nations Security Council (UNSC) (2008‐12) and its subsequent term on the Council (2013‐14) both encouraged and impacted on the country's engagement with Africa. Drawing on extensive interviews with senior Australian politicians and government officials with intimate knowledge of the country's campaign for the UNSC and its time on the Council, as well as with senior African diplomats, the article contributes new knowledge on how Canberra campaigned to secure African UN votes and how it engaged with the Council's Africa‐dominated agenda. The article concludes by evaluating the legacy of this period of high engagement for both ongoing Australia‐Africa relations and Australia's new campaign for a UNSC seat during the 2029‐30 term.